Design and development mini compression molding for teaching and learning - Sullyfaizura Mohd Rawi; Suzilawati Alias; Siti Aishah Wahid (Education and Social Sciences Review, 2020)
Compression molding is a major technology in the plastic industry, and the one of the original processing techniques for manufacturing plastic. The current study was aimed to design and fabrication of mini compression molding machine for use in laboratory workshop or education institution. This machine was designed and fabricated to reduce the cost of expensive purchasing and cost maintenance of compression molding machines used in the industry. Mini compression molding provides for study of implemented to facilitate the production process of plastic products according to the mold provided. This machine used an oven as a heater to melt the resin in the mold provided and car jack as pressure to compress the resin after melting. The parameter has been considered is a temperature and pressure of the process of flow raw material into the cavity and period time of melting. Based on the test, the optimize of temperature suitable for heating the polypropylene plastic (PP) to melt is at 250°C, while the best time to melt of at 250°C is within 15 minutes. From the results obtained based on the quality of mold produced by the mini compression molding machine, the fabricated machine performance was satisfactory and can be used locally institution and industrially in small scale. This Mini compression molding used in Manufacturing lab in PSMZA for subject of DJF2012 (Manufacturing Workshop Practice 2) as development aids in Teaching and Learning.